Efficacy and safety of peroral endoscopic myotomy for esophageal diverticula - Wessels Wessels; Schuitenmaker Schuitenmaker; Bastiaansen Bastiaansen; Fockens Fockens; Masclee Masclee; Bredenoord Bredenoord (Endoscopy International Open, 2023)
Background and study aims Epiphrenic diverticula are rare and mainly occur in patients with underlying esophageal motility disorders. The current standard treatment is surgical diverticulectomy often combined by myotomy and is associated with significant adverse event (AE) rates. The aim of this study was to examine the efficacy and safety of peroral endoscopic myotomy in reducing esophageal symptoms in patients with esophageal diverticula.